Harry's horses: Resistances to colonial authorities (2009)
This article intends to illustrate the relationships between the Indigenous people of Australia and the Aboriginal Welfare Board, the colonial administration which was in charge of the Aboriginal population of New South Wales until the end of the 1960s. I will present a specific case of resistance to the conditions of subordination : a conflict between Harry Combo, a resident of one of the Board's missions and the manager in charge of that mission, J. B. Stratton. This example is a good illustration of the kind of interactions that were taking place between various white authorities (managers, Welfare Officers, Sydney bureaucrats) and the Aboriginal people living in the governmental missions. I would like to show that, by focussing on a singular (or atypical) case, one can shed new light on everyday practices of colonial domination.